2021
DOI: 10.1186/s12931-020-01585-9
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol drug delivery to spontaneously-breathing preterm neonates: lessons learned

Abstract: Delivery of medications to preterm neonates receiving non-invasive ventilation (NIV) represents one of the most challenging scenarios for aerosol medicine. This challenge is highlighted by the undersized anatomy and the complex (patho)physiological characteristics of the lungs in such infants. Key physiological restraints include low lung volumes, low compliance, and irregular respiratory rates, which significantly reduce lung deposition. Such factors are inherent to premature birth and thus can be regarded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 184 publications
0
34
0
5
Order By: Relevance
“…Clinical data are still scarce. In total, 3 pilot studies [58,60,69], a phase 1 clinical study [59] and a subsequent phase 2 clinical trial [70], and 4 RCTs have been published, comprising an overall number of 909 preterm infants (Table 2) [57,59,71,72]. While all studies documented feasibility and safety, inconsistent results were found concerning efficacy.…”
Section: Preclinical and Clinical Evidence For Aerosolized Surfactantmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical data are still scarce. In total, 3 pilot studies [58,60,69], a phase 1 clinical study [59] and a subsequent phase 2 clinical trial [70], and 4 RCTs have been published, comprising an overall number of 909 preterm infants (Table 2) [57,59,71,72]. While all studies documented feasibility and safety, inconsistent results were found concerning efficacy.…”
Section: Preclinical and Clinical Evidence For Aerosolized Surfactantmentioning
confidence: 99%
“…Given that aerosol groups were compared to historical controls, however, conclusion about efficacy is limited [70]. Very recently, a multicenter RCT in 129 infants with mild-to-moderate RDS compared nCPAP with 2 different dosing regimens of nebulized surfactant with nCPAP alone [72]. The authors found no reduction in the likelihood of respiratory failure within the first 72 h of life, and the trial was stopped early due to limited effect of the intervention [72].…”
Section: Preclinical and Clinical Evidence For Aerosolized Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is the approach of standard aerosolizers, such as the Aerogen ® (Aerogen Ltd., Galway, Ireland), to synchronize aerosol production with breathing, feeding the aerosol into the inhalation limb. However, since the distance from the nebulizer to the patient is large, respiration-synchronized aerosol delivery is not possible due to the considerable delay before the aerosol reaches the patient [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that for the highest possible inhaled aerosol efficiency the aerosol must also be administered as close as possible to the patient interface [ 25 ]. The greater the distance between the release of the aerosol into the patient interface, the less efficient the delivery due to the longer aerosol path length and thus increased deposition on the walls and a delay in aerosol arrival [ 1 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%